If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + 20) = 60 Reorder the terms: 3x(20 + x) = 60 (20 * 3x + x * 3x) = 60 (60x + 3x2) = 60 Solving 60x + 3x2 = 60 Solving for variable 'x'. Reorder the terms: -60 + 60x + 3x2 = 60 + -60 Combine like terms: 60 + -60 = 0 -60 + 60x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-20 + 20x + x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-20 + 20x + x2)' equal to zero and attempt to solve: Simplifying -20 + 20x + x2 = 0 Solving -20 + 20x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '20' to each side of the equation. -20 + 20x + 20 + x2 = 0 + 20 Reorder the terms: -20 + 20 + 20x + x2 = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 20x + x2 = 0 + 20 20x + x2 = 0 + 20 Combine like terms: 0 + 20 = 20 20x + x2 = 20 The x term is 20x. Take half its coefficient (10). Square it (100) and add it to both sides. Add '100' to each side of the equation. 20x + 100 + x2 = 20 + 100 Reorder the terms: 100 + 20x + x2 = 20 + 100 Combine like terms: 20 + 100 = 120 100 + 20x + x2 = 120 Factor a perfect square on the left side: (x + 10)(x + 10) = 120 Calculate the square root of the right side: 10.95445115 Break this problem into two subproblems by setting (x + 10) equal to 10.95445115 and -10.95445115.Subproblem 1
x + 10 = 10.95445115 Simplifying x + 10 = 10.95445115 Reorder the terms: 10 + x = 10.95445115 Solving 10 + x = 10.95445115 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = 10.95445115 + -10 Combine like terms: 10 + -10 = 0 0 + x = 10.95445115 + -10 x = 10.95445115 + -10 Combine like terms: 10.95445115 + -10 = 0.95445115 x = 0.95445115 Simplifying x = 0.95445115Subproblem 2
x + 10 = -10.95445115 Simplifying x + 10 = -10.95445115 Reorder the terms: 10 + x = -10.95445115 Solving 10 + x = -10.95445115 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = -10.95445115 + -10 Combine like terms: 10 + -10 = 0 0 + x = -10.95445115 + -10 x = -10.95445115 + -10 Combine like terms: -10.95445115 + -10 = -20.95445115 x = -20.95445115 Simplifying x = -20.95445115Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.95445115, -20.95445115}Solution
x = {0.95445115, -20.95445115}
| 5(x+3)-(x-7)= | | -4(-14-19a)=7(11a+20)-a | | (6+w)(3w+7)=0 | | 3x+8y=9(y+2y+7) | | 13c+51c=-26 | | -11=x+8x+7 | | 5y+5=y(8-2y) | | 13(x-3)-22x=-18 | | v=3.14(3.14)(h) | | x+18+2x=-14-2x-18 | | X+(2x+0.10)=2.5 | | 2x+n=3 | | 95+52a=303 | | y=x^2-11x+20 | | 0.5x+0.4=0.08x-0.5 | | 5b+20=1.75 | | 6x-4=3x-28 | | 3x^2+23=4 | | -3+t=19 | | -4(3x-9)+6(2x+7)= | | 36-(2c+3)=2(c+4)+c | | v=3.14h | | 4y-25=15 | | 7x+8=107-2x | | 9+4x-5=-8 | | 7s^2+48s-7= | | 8+3x=x+2 | | 7+22=33-4 | | -84=7(-5-x) | | 9b+8b-13=106 | | 4x+2=y | | 3(x+5)+2(4x-7)= |